Pangenome analysis of Bifidobacterium longum and site-directed mutagenesis through by-pass of restriction-modification systems. (December 2015) - O'Callaghan, A.; Bottacini, F.; O'Connell Motherway, M.; van Sinderen, D.
Abstract Background Bifidobacterial genome analysis has provided insights as to how these gut commensals adapt to and persist in the human GIT, while also revealing genetic diversity among members of a given bifidobacterial (sub)species. Bifidobacteria are notoriously recalcitrant to genetic modification, which prevents exploration of their genomic functions, including those that convey (human) health benefits. Methods PacBio SMRT sequencing was used to determine the whole genome seqeunces of twoB. longum subsp.longum strains. TheB. longum pan-genome was computed using PGAP v1.2 and the coreB. longum phylogenetic tree was constructed using a maximum-likelihood based approach in PhyML v3.0.M.blmNCII was cloned inE. coli and an internal fragment ifarfB arfB was cloned into pORI19 for insertion mutagenesis. Results In this study we present the complete genome sequences of twoBifidobacterium longum subsp.longum strains. Comparative analysis with thirty one publicly availableB. longum genomes allowed the definition of theB. longum core and dispensable genomes. This analysis also highlighted differences in particular metabolic abilities between members of theB. longum subspeciesinfantis, longum andsuis . Furthermore, phylogenetic analysis of theB. longum core genome indicated the existence of a novel subspecies. Methylome data, coupled to the analysis of restriction-modification systems, allowed us to substantially increase the genetic accessibility ofB. longum subsp.longum NCIMB 8809 to a level that was shown to permit site-directed mutagenesis. Conclusions Comparative genomic analysis of thirty threeB. longum representatives revealed a closed pan-genome for this bifidobacterial species. Phylogenetic analysis of theB. longum core genome also provides evidence for a novel fifthB. longum subspecies. Finally, we improved genetic accessibility for the strainB. longum subsp.longum NCIMB 8809, which allowed the generation of a mutant of this strain.